Graphite steel wire rod for TV pam nut parts, graphite steel, its manufacturing method and cutting method

A controlled composition and heat treatment process for graphite steel wire rods with uniform graphite distribution address commercialization challenges, enhancing machinability and enabling production of high-performance small parts.

JP2024546140AActive Publication Date: 2024-12-17POHANG IRON & STEEL CO LTD
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
JP2024535601
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2021-12-14
Filing Date
2022-12-13
Publication Date
2024-12-17
Estimated Expiration
2042-12-13

AI Technical Summary

Technical Problem

Existing graphite-free cutting steels face challenges in commercialization due to uneven graphite distribution, which affects machinability and tool life, and the use of harmful elements like Pb leads to environmental hazards and production difficulties.

Method used

A graphite steel wire rod composition of C: 0.60-0.79%, Si: 2.0-2.5%, Mn: 0.7-1.3%, S: 0.2-0.5%, Al: 0.01-0.05%, Ti: 0.005-0.02%, N: 0.003-0.015%, P: 0.0001-0.015%, with a fine structure and uniform graphite distribution, achieved through controlled heat treatment and rolling processes.

Benefits of technology

The solution ensures excellent cutting performance, eliminating environmental hazards and improving machinability, tool life, and enabling production of small parts like TV pum nuts.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2024546140000001
    Figure 2024546140000001
  • Figure 2024546140000002
    Figure 2024546140000002
  • Figure 2024546140000003
    Figure 2024546140000003
Patent Text Reader

Abstract

The present invention aims to provide a component design and cutting conditions for graphite steel for manufacturing industrial parts, and to provide a steel wire rod, a manufacturing method of graphite steel, and a graphitization heat treatment for manufacturing graphite steel. [Solution] A method for producing a graphite steel wire rod for TV pum nut parts includes the steps of producing a billet containing, by weight, 0.60-0.79% carbon (C), 2.0-2.5% silicon (Si), 0.7-1.3% manganese (Mn), 0.2-0.5% sulfur (S), 0.01-0.05% aluminum (Al), 0.005-0.020% titanium (Ti), 0.003-0.015% nitrogen (N), 0.0001-0.015% phosphorus (P), and the remainder being iron (Fe) and unavoidable impurities; The method includes the steps of heating a billet, hot rolling the heated billet to produce a wire rod, and cooling the wire rod, wherein the heating step includes heat treatment at a temperature of 1050±100° C. for 60 minutes or more, the hot rolling step includes hot rolling at a temperature of 900 to 1150° C., and the cooling step includes cooling to 500° C. at a cooling rate of 0.1 to 10.0° C. / s, and further includes an air-cooling step after the cooling step.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a graphite steel wire rod, graphite steel, and its manufacturing and cutting method for TV pan nut parts, and more particularly to a cutting method for manufacturing industrial parts, and to a graphite steel wire rod, graphite steel, and its manufacturing method for the same. [Background technology]

[0002] A PEM nut, also known as a self-clinching nut, is used to connect materials such as thin plates and sheet metal. It has a rounded shape, an embossed gear and a guide groove on one end. It is a nut that can be attached to a thin plate by clinching a high-strength internal thread. Generally, free-cutting steels with machinability-imparting elements such as Pb, Bi, and S are used as materials for machine parts and other objects that require machinability. To improve the machinability of steel, low-melting-point machinability-imparting elements such as Pb and Bi are added to the steel to utilize the liquid metal bromide phenomenon, or a large amount of MnS is formed in the steel. This type of free-cutting steel has excellent machinability, including surface roughness, chip treatment, and tool life during cutting.

[0003] However, free-cutting steels with added Pb, which has the best machinability, have the problem that they emit harmful substances such as toxic fumes during cutting, which are very harmful to the human body and are also very disadvantageous in recycling steel.As a result, the addition of S, Bi, Te, Sn, etc. has been proposed as an alternative, but it has been known that there are problems with these, such as the tendency for cracks to occur during steel manufacturing, making production very difficult, or the occurrence of cracks during hot rolling.

[0004] Graphite free-cutting steel has been developed to solve the above problems. Graphite free-cutting steel is a steel containing fine graphite grains inside a ferrite matrix or a ferrite and pearlite matrix, and the fine graphite grains inside act as a crack source and chip breaker during cutting, resulting in good machinability.

[0005] However, despite these advantages of graphite free-cutting steel, it has not been commercialized yet because, when carbon is added to steel, graphite is precipitated as a metastable phase, cementite, even though graphite is a stable phase, and it is difficult to precipitate graphite without a separate long-term heat treatment, and decarburization occurs during such a long-term heat treatment process, which has a detrimental effect on the performance of the final product.

[0006] Furthermore, even if graphite grains are precipitated through graphitization heat treatment, if they are unevenly distributed in irregular shapes, the distribution of physical properties during cutting is uneven, resulting in very poor chip processing and surface roughness, and shortened tool life, making it difficult to obtain the advantages of graphite free-cutting steel. Therefore, it is necessary to provide a graphite free-cutting steel wire that can distribute fine graphite steel uniformly within the matrix during heat treatment while significantly shortening the heat treatment time, and a cutting method with excellent machinability (i.e., CNC compound lathe, CAM automatic lathe) [Prior art documents] [Patent documents]

[0007] [Patent Document 1] Korean Patent Publication No. 10-2015-0057400 Summary of the Invention [Problem to be solved by the invention]

[0008] The present invention aims to provide a component design and cutting conditions for graphite steel for manufacturing industrial parts, and to provide a steel wire rod, a manufacturing method of graphite steel, and a graphitization heat treatment for manufacturing graphite steel.

[0009] However, the problems to be solved by the present application are not limited to those mentioned above, and other problems not mentioned will be clearly understood by those skilled in the art from the description below. [Means for solving the problem]

[0010] The graphite steel wire rod of the present invention contains, by weight, 0.60-0.79% carbon (C), 2.0-2.5% silicon (Si), 0.7-1.3% manganese (Mn), 0.2-0.5% sulfur (S), 0.01-0.05% aluminum (Al), 0.005-0.02% titanium (Ti), 0.003-0.015% nitrogen (N), and 0.0001-0.015% phosphorus (P), with the remainder being iron (Fe) and unavoidable impurities.

[0011] A method for producing a graphite steel wire rod of the present invention includes the steps of producing a billet containing, by weight, 0.60 to 0.79% carbon (C), 2.0 to 2.5% silicon (Si), 0.7 to 1.3% manganese (Mn), 0.2 to 0.5% sulfur (S), 0.01 to 0.05% aluminum (Al), 0.005 to 0.02% titanium (Ti), 0.003 to 0.015% nitrogen (N), 0.0001 to 0.015% phosphorus (P), and the balance being iron (Fe) and unavoidable impurities, heating the billet, hot-rolling the heated billet to produce a wire rod, and cooling the wire rod.

[0012] The graphite steel of the present invention contains, by weight, 0.60 to 0.79% carbon (C), 2.0 to 2.5% silicon (Si), 0.7 to 1.3% manganese (Mn), 0.2 to 0.5% sulfur (S), 0.01 to 0.05% aluminum (Al), 0.005 to 0.02% titanium (Ti), 0.003 to 0.015% nitrogen (N), and 0.0001 to 0.015% phosphorus (P), with the remainder being iron (Fe) and unavoidable impurities. The graphite steel has a fine structure with graphite grains distributed in a ferrite matrix, a graphitization rate of 90% or more, and a pearlite fraction of less than 10%.

[0013] A method for producing graphite steel of the present invention includes the steps of producing a wire rod containing, by weight, 0.60-0.79% carbon (C), 2.0-2.5% silicon (Si), 0.7-1.3% manganese (Mn), 0.20-0.5% sulfur (S), 0.01-0.05% aluminum (Al), 0.005-0.02% titanium (Ti), 0.003-0.015% nitrogen (N), 0.0001-0.015% phosphorus (P), and the balance being iron (Fe) and unavoidable impurities, and performing a graphitization heat treatment on the produced wire rod.

[0014] The cutting method of the present invention is characterized in that the graphite steel is cut by any one selected from a CNC combined lathe and a CAM automatic lathe. Effect of the Invention

[0015] The graphite free-cutting steel of the present invention has excellent cutting performance and can be used as a material for small parts such as TV panel nuts. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0016] The graphite steel wire rod of the present invention contains, by weight, 0.60-0.79% carbon (C), 2.0-2.5% silicon (Si), 0.7-1.3% manganese (Mn), 0.2-0.5% sulfur (S), 0.01-0.05% aluminum (Al), 0.005-0.02% titanium (Ti), 0.003-0.015% nitrogen (N), and 0.0001-0.015% phosphorus (P), with the remainder being iron (Fe) and unavoidable impurities.

[0017] Hereinafter, preferred embodiments of the present invention will be described. However, the embodiments of the present invention may be modified into various other forms, and the technical concept of the present invention is not limited to the embodiments described below. Furthermore, the embodiments of the present invention are provided to more completely explain the present invention to those having average knowledge in the art.

[0018] The terms used in this application are merely used to describe specific examples. For example, a singular expression includes a plural expression unless the context clearly requires a singular expression.

[0019] In the following, unless otherwise specified, the unit is % by weight. Furthermore, when a part is described as "comprising" a certain component, this does not mean that other components are excluded, but that other components may be further included, unless otherwise specified.

[0020] Meanwhile, unless otherwise defined, all terms used herein should be considered to have the same meaning as that commonly understood by a person having ordinary skill in the art to which the present invention belongs. Therefore, unless clearly defined herein, specific terms should not be interpreted as having an overly ideal or formal meaning. For example, in this specification, singular expressions include plural expressions unless there is a clear exception in the context.

[0021] In addition, in this specification, the terms "about," "substantially," and the like are used in the sense of a numerical value or close to a numerical value when the tolerances of manufacturing and materials inherent in the referred meaning are presented, and are used to prevent unconscionable infringers from unfairly exploiting the disclosure in which precise or absolute numerical values ​​are referred to in order to aid in the understanding of the present invention.

[0022] Hereinafter, the graphite steel wire rod for TV pan nut parts, graphite steel having excellent cutting performance, and a manufacturing method thereof and a cutting method thereof according to the present invention will be described in detail.

[0023] <Graphite steel wire rod>

[0024] The graphite steel wire rod of the present invention contains, by weight, 0.60-0.79% carbon (C), 2.0-2.5% silicon (Si), 0.7-1.3% manganese (Mn), 0.2-0.5% sulfur (S), 0.01-0.05% aluminum (Al), 0.005-0.02% titanium (Ti), 0.003-0.015% nitrogen (N), and 0.0001-0.015% phosphorus (P), with the remainder being iron (Fe) and unavoidable impurities.

[0025] Carbon (C): 0.60~0.79% by weight

[0026] Carbon is an essential element for forming graphite grains. If the carbon content is less than 0.60 wt%, the effect of improving machinability is insufficient and the distribution of graphite grains is non-uniform even after graphitization is completed. On the other hand, if the carbon content exceeds 0.79 wt%, the graphite grains are generated coarsely and the aspect ratio increases, which may deteriorate machinability, especially surface roughness. Therefore, the upper limit of the carbon content is preferably 0.79 wt%.

[0027] Silicon (Si): 2.0-2.5% by weight

[0028] Silicon is an essential component as a deoxidizer during the manufacture of molten steel, and is a graphitization-promoting element that destabilizes cementite in steel so that carbon precipitates as graphite, and is therefore actively added. In order to achieve this effect in the present invention, the silicon content is preferably 2.0 wt%. However, if the silicon content is excessive, not only will the effect saturate, but the hardness will increase due to the solid solution strengthening effect, accelerating tool wear during cutting, and brittleness will be induced due to an increase in non-metallic inclusions, which may cause excessive decarburization during hot rolling. Therefore, the upper limit of the silicon content is preferably 2.5 wt%.

[0029] Manganese (Mn): 0.7 to 1.3% by weight

[0030] Manganese improves the strength and impact properties of steel, and combines with sulfur in steel to form MnS inclusions, thereby contributing to improved machinability. In order to achieve this effect in the present invention, it is preferable that manganese is contained in an amount of 0.7 wt% or more. However, if the content is too high, it may inhibit graphitization, delay the completion time of graphitization, and increase strength and hardness, thereby decreasing machinability. Therefore, the upper limit of the manganese content is preferably 1.3 wt%.

[0031] Sulfur (S): 0.2~0.5% by weight

[0032] Sulfur can improve machinability by combining with manganese and inducing the formation of MnS inclusions. However, if sulfur is contained in excess, it not only inhibits the graphitization of carbon in steel, but also segregates at grain boundaries to reduce toughness, forms low melting point sulfides to inhibit hot rolling, and MnS elongated by rolling may cause mechanical anisotropy. Therefore, in the present invention, it is preferable to appropriately adjust the content of sulfur so that the physical properties are not inhibited by sulfur and the machinability can be improved. Specifically, if the sulfur content is less than 0.2 wt%, the amount of inclusions such as MnS is not sufficiently generated, resulting in poor machinability, so it must be controlled to be more than that. However, if the sulfur content exceeds 0.5 wt%, there is a possibility of quality defects such as surface defects occurring, so it must be controlled to be less than that.

[0033] Aluminum (Al): 0.01 to 0.05% by weight

[0034] Aluminum is the element that promotes graphitization next to silicon. This is because aluminum destabilizes cementite when it exists as solid solution Al, and therefore it is necessary for aluminum to exist as solid solution Al. In order to exhibit such an effect in the present invention, it is preferable that aluminum is contained in an amount of 0.01 wt% or more. On the other hand, if the content is excessive, not only the effect is saturated, but also nozzle clogging may be induced during continuous casting, and AlN is generated at the austenite grain boundaries, and graphite using this as a nucleus is unevenly distributed at the grain boundaries. Therefore, the upper limit of the aluminum content is preferably 0.05 wt%.

[0035] Titanium (Ti): 0.005 to 0.020% by weight

[0036] Titanium combines with nitrogen to form nitrides such as TiN and AlN, as does aluminum, and these nitrides act as nuclei for graphite formation during isothermal heat treatment. However, since AlN has a low formation temperature, it precipitates unevenly at grain boundaries after austenite is formed, whereas TiN has a higher formation temperature than AlN and crystallizes before the formation of austenite is completed, so it is uniformly distributed at grain boundaries and within austenite. Therefore, the graphite grains formed with TiN as a nucleation site are fine and uniformly distributed. To achieve this effect, it is preferable that the titanium content is 0.005% by weight or more, but if the content exceeds 0.020%, it may become coarse carbonitrides, consuming carbon necessary for graphite formation and inhibiting graphitization. Therefore, the upper limit of the titanium content is preferably 0.020% by weight.

[0037] Nitrogen (N): 0.003 to 0.015% by weight

[0038] Nitrogen combines with titanium and aluminum to produce TiN, AlN, etc., and in particular, nitrides such as AlN are mainly formed at the austenite grain boundaries. During graphitization heat treatment, graphite is formed with these nitrides as nuclei, which can cause uneven distribution of graphite, so it is necessary to add an appropriate amount. If the amount of nitrogen added is too much and it cannot combine with nitride-forming elements and exists in the steel as solid solution nitrogen, it will have a harmful effect of increasing strength, stabilizing cementite, and delaying graphitization. Therefore, in order to consume it to form nitrides that act as graphite nucleation sites and not remain as solid solution nitrogen, the present invention limits the amount of nitrogen to 0.003% by weight as the lower limit and 0.015% by weight as the upper limit.

[0039] Phosphorus (P): 0.0001 to 0.015% by weight

[0040] When a small amount of phosphorus is contained, it weakens the grain boundaries of steel, which is useful for machinability. However, when contained in an excessive amount, it increases the hardness of ferrite due to the solid solution strengthening effect, reduces the toughness and delayed fracture resistance of the steel material, and promotes the occurrence of surface defects, so it is preferable to control its content as low as possible within the range of 0.0001 to 0.015% by weight. In particular, it is important to control the upper limit, and in the present invention, the upper limit is controlled at 0.015% by weight.

[0041] Other Ingredients

[0042] The remaining component of the present invention is iron (Fe). However, since unintended impurities may be inevitably mixed in from the raw materials or the surrounding environment during normal manufacturing processes, it is not possible to exclude these. However, it is preferable that the present invention is substantially free of boron (B) and oxygen (O). These impurities are known to anyone who is an engineer of normal manufacturing processes, and therefore all of their contents will not be specifically mentioned in this specification.

[0043] <Microstructure>

[0044] Also, according to the present invention, the graphite steel wire rod may have an area fraction of pearlite of 90% or more and an area fraction of ferrite of less than 10%, but it is preferable that the area fraction of pearlite is 95% or more and the area fraction of ferrite is less than 5%. In the present invention, since graphite grains are generated by decomposition of pearlite, if the area fraction of pearlite is low, the graphite grain fraction is also low, which is undesirable since it shows a non-uniform distribution. Since a higher area fraction of pearlite is advantageous for ensuring uniform and fine graphite grains, the upper limit is not particularly limited.

[0045] The graphite steel wire manufacturing method, graphite steel, graphite steel manufacturing method, and cutting method described below may all be applied to the graphite steel wire described above, and although detailed descriptions of overlapping parts are omitted, they may be equally applied even if the descriptions are omitted.

[0046] <Graphite steel wire manufacturing method>

[0047] A method for producing a graphite steel wire rod of the present invention includes the steps of producing a billet containing, by weight, 0.60 to 0.79% carbon (C), 2.0 to 2.5% silicon (Si), 0.7 to 1.3% manganese (Mn), 0.2 to 0.5% sulfur (S), 0.01 to 0.05% aluminum (Al), 0.005 to 0.02% titanium (Ti), 0.003 to 0.015% nitrogen (N), 0.0001 to 0.015% phosphorus (P), and the balance being iron (Fe) and unavoidable impurities, heating the billet, hot-rolling the heated billet to produce a wire rod, and cooling the wire rod.

[0048] heating process

[0049] In addition, the heating step of the present invention may include maintaining the heat treatment at a temperature in the range of 1050±100° C. for 60 minutes or more.

[0050] Before hot rolling the billet, it is maintained at a temperature in the range of 1050±100°C for at least 60 minutes. If the billet heating temperature is less than 950°C, the load increases during rolling and rolling productivity may decrease, so there are disadvantages to a low heating temperature. If the heating temperature exceeds 1150°C, not only does it increase costs, but it is also undesirable because the decarburization is accelerated and the decarburized layer becomes thicker and remains in the final product. The reason for setting the heating maintenance time at 60 minutes or more is that it is difficult to ensure uniform temperature distribution inside and outside the billet for rolling wire rod if it is less than 60 minutes.

[0051] Rolling process

[0052] In addition, the step of hot rolling to produce a wire rod according to the present invention may include hot rolling at a temperature range of 900 to 1150°C.

[0053] The reason for the wire rod rolling temperature being set in the range of 900 to 1150°C is that if the temperature is less than 900°C, surface scratches are likely to occur during hot rolling, the rolling load increases, and rolling becomes difficult, whereas if the temperature exceeds 1150°C, the AGS (Austenite Grain Size) becomes coarse, which may lengthen the graphitization heat treatment time after wire rod rolling.

[0054] cooling process

[0055] In addition, the cooling step of the present invention may include cooling to 500°C at a cooling rate of 0.1 to 10.0°C / s, and specifically, may be cooling to 500°C at a cooling rate of 0.1 to 10.0°C / s in a temperature range of 750 to 900°C.

[0056] In addition, the present invention may include an air-cooling step after the cooling step.

[0057] A cooling rate exceeding 10.0°C / s is not preferred because a hard phase such as martensite is generated, which may cause wire breakage during cold drawing, which is the next process after wire rolling, and a cooling rate of less than 0.1°C / s is not preferred because an excessive amount of niter phase is generated, which may reduce the pearlite fraction or coarsen the crystal grains, resulting in non-uniform distribution of graphite grains generated after graphitization heat treatment.

[0058] <Graphite steel>

[0059] The graphite steel of the present invention includes, by weight, 0.60 to 0.79% carbon (C), 2.0 to 2.5% silicon (Si), 0.7 to 1.3% manganese (Mn), 0.2 to 0.5% sulfur (S), 0.01 to 0.05% aluminum (Al), 0.005 to 0.02% titanium (Ti), 0.003 to 0.015% nitrogen (N), 0.0001 to 0.015% phosphorus (P), with the remainder being iron (Fe) and unavoidable impurities, has a fine structure, graphite grains distributed in a ferrite matrix, a pearlite fraction of less than 10%, and a graphitization rate of 90% or more.

[0060] The graphitization rate of the graphite steel of the present invention may be preferably 95% or more, and more preferably 99%.

[0061] Meanwhile, the graphitization ratio means the ratio of the carbon content existing in a graphite state to the carbon content added to the steel, and is defined by the following relational expression 1.

[0062] [Relationship 1] Graphitization rate (%) = (1 - carbon content in undecomposed pearlite / carbon content in steel) x 100

[0063] (If there is no undecomposed pearlite, the graphitization rate will be 100%)

[0064] The graphitization rate of 90% or more means that most of the added carbon has been consumed to generate graphite, and that there is no undecomposed pearlite, i.e., the material has a fine structure in which graphite grains are distributed in a ferrite matrix. At this time, the amount of carbon dissolved in ferrite and carbon dissolved in fine carbides is very small and is therefore not taken into consideration.

[0065] <Graphite steel manufacturing method>

[0066] A method for producing graphite steel of the present invention includes the steps of producing a wire rod containing, by weight, 0.60-0.79% carbon (C), 2.0-2.5% silicon (Si), 0.7-1.3% manganese (Mn), 0.2-0.5% sulfur (S), 0.01-0.05% aluminum (Al), 0.005-0.02% titanium (Ti), 0.003-0.015% nitrogen (N), 0.0001-0.015% phosphorus (P), and the balance being iron (Fe) and unavoidable impurities, and performing a graphitization heat treatment on the produced wire rod.

[0067] Also, according to the present invention, the graphitization heat treatment step may include heat treatment at a temperature range of 700 to 800° C. for 5 hours or more, preferably 5 to 20 hours.

[0068] If the wire is heat-treated for 5 hours or more at a temperature of 700 to 800° C., the graphitization rate can reach 90% or more. If the temperature is less than 700° C., the graphitization heat treatment time is extended to more than 20 hours, and if the temperature is more than 800° C., the graphitization time is extended, which is not preferable.

[0069] <Cutting method>

[0070] The cutting method of the present invention is characterized in that the graphite steel according to the present invention is cut by any one selected from a CNC combined lathe and a CAM automatic lathe.

[0071] In addition, according to the present invention, the CNC multi-purpose lathe may have a cutting speed of 1500 RPM or more and a feed speed of 0.03 mm / rev or more, and the CAM automatic lathe may also have a cutting speed of 1500 RPM or more and a feed speed of 0.03 mm / rev or more.

[0072] The graphite free-cutting steel wire rod thus produced is cut by a cutting company to produce small industrial parts, such as TV panel nuts. If it does not have the same cutting performance as general free-cutting steel, it will be impossible to enter the market. To overcome this, the present invention provides a method of manufacturing the steel by cutting under the conditions of a cutting speed of a CNC combined lathe and / or a CAM type automatic lathe of 1500 RPM or more and a transfer speed of 0.03 mm / rev or more. If the cutting speed of the CNC combined lathe and / or the CAM type automatic lathe is less than 1500 RPM and / or a transfer speed of less than 0.03 mm / rev, the cutting performance will be reduced. The faster the cutting speed and the transfer speed, the better the cutting performance will be, and the steel will be able to show a level equivalent to that of general free-cutting steel.

[0073] The present invention will now be described in more detail with reference to examples.

[0074] The following examples are presented to fully convey the concept of the present invention to those skilled in the art to which the present invention pertains, and the present invention is not limited to the examples presented herein and may be embodied in other forms.

[0075] <Example>

[0076] A billet having the composition shown in Table 1 below was maintained at a heating temperature of 1050° C. for 90 minutes and subjected to high speed wire rolling to produce wires of Examples 1 to 11 and Comparative Examples 1 to 7 having a diameter of 19 mm.

[0077] [Table 1]

[0078] In addition, in the manufacture of the wire, the wire was cooled after rolling to produce the wire, and the pearlite area fraction in the microstructure was measured. The cooling start temperature, cooling rate, and pearlite area fraction are shown in Table 2 below.

[0079] The wire rod was subjected to a graphitization heat treatment, during which the graphitization heat treatment duration and graphitization rate were measured and shown in Table 2. The graphitization heat treatment temperature was constantly set at "temperature -50°C" to perform the graphitization heat treatment.

[0080] [Table 2]

[0081] In Table 2, the (100%-graphitization rate) structure is composed of MnS inclusions, pearlite, and some inclusions that are normally present, and the graphitized structure is composed of ferrite and graphite grains.

[0082] It can be seen that the pearlite fraction and graphitized fraction are achieved under the manufacturing conditions of wire rod and graphitized material as shown in Table 2 above.

[0083] In addition, examples and comparative examples according to cutting conditions for manufacturing TV pumnut parts are shown in Tables 3 and 4 below. Table 3 shows the CNC lathe machining conditions, and Table 4 shows the lathe machining conditions.

[0084] [Table 3]

[0085] [Table 4]

[0086] In Tables 3 and 4, the machinability is a numerical value based on the cutting performance of general free-cutting steel (100% means the same level).

[0087] The examples and comparative examples are evaluated with reference to Tables 1 to 4 below.

[0088] It can be confirmed that Examples 1 to 11 satisfy the alloy composition range and the cooling rate of 0.1 to 10° C. / s of the present invention, and therefore the pearlite area fraction of the graphite steel wire is 95.1% or more, and the graphitization rate is 97.5% or more. On the other hand, it can be confirmed that Comparative Examples 1 to 7, which have a cooling rate outside the range of 0.1 to 10° C. / s, have a pearlite area fraction of only 93.0 to 94.2% and a graphitization rate of only 75 to 86%.

[0089] In addition, Examples 1 to 11, which satisfy the conditions of a cutting speed of 1500 RPM or more and a transfer speed of 0.03 mm / rev or more on the CNC multi-purpose lathe and CAM automatic lathe, are evaluated as having cutting performance at the same level as general free-cutting steel (100% compared to general free-cutting steel) through material cutting processing, while Comparative Examples 1 to 7, which do not satisfy the above cutting speed and transfer speed conditions, are confirmed to have cutting performance that is only 80 to 95% of that of general free-cutting steel.

[0090] Although exemplary embodiments of the present invention have been described above, the present invention is not limited thereto, and it should be understood that various changes and modifications can be made by those skilled in the art without departing from the concept and scope of the following claims. [Industrial Applicability]

[0091] The graphite free-cutting steel of the present invention does not generate fumes and has excellent cutting performance, so it can be used as a material for small parts such as TV panel nuts, and is therefore recognized to have industrial applicability.

Claims

1. Graphite steel wire for TV pum nut parts, characterized in that it contains, by weight, 0.60 to 0.79% carbon (C), 2.0 to 2.5% silicon (Si), 0.7 to 1.3% manganese (Mn), 0.2 to 0.5% sulfur (S), 0.01 to 0.05% aluminum (Al), 0.005 to 0.020% titanium (Ti), 0.003 to 0.015% nitrogen (N), and 0.0001 to 0.015% phosphorus (P), with the remainder being iron (Fe) and unavoidable impurities.

2. 2. The graphite steel wire for TV pum nut parts according to claim 1, characterized in that the area fraction of pearlite is 95% or more.

3. producing a billet containing, in weight percent, 0.60-0.79% carbon (C), 2.0-2.5% silicon (Si), 0.7-1.3% manganese (Mn), 0.2-0.5% sulfur (S), 0.01-0.05% aluminum (Al), 0.005-0.020% titanium (Ti), 0.003-0.015% nitrogen (N), 0.0001-0.015% phosphorus (P), with the balance being iron (Fe) and unavoidable impurities; heating the billet; hot rolling the heated billet into a wire rod; and cooling the wire.

4. 4. The method of claim 3, wherein the heating step comprises maintaining the temperature in the range of 1050±100° C. for 60 minutes or more to perform heat treatment.

5. 4. The method of claim 3, wherein the hot rolling to produce a wire comprises hot rolling at a temperature in the range of 900 to 1150° C.

6. 4. The method of claim 3, wherein the cooling step comprises cooling the wire to 500° C. at a cooling rate of 0.1 to 10.0° C. / s.

7. 4. The method of claim 3, further comprising the step of air-cooling after the step of cooling.

8. The composition contains, by weight, 0.60-0.79% carbon (C), 2.0-2.5% silicon (Si), 0.7-1.3% manganese (Mn), 0.2-0.5% sulfur (S), 0.01-0.05% aluminum (Al), 0.005-0.02% titanium (Ti), 0.003-0.015% nitrogen (N), 0.0001-0.015% phosphorus (P), and the remainder being iron (Fe) and unavoidable impurities; A graphite steel for TV pum nut parts, characterized in that it has a fine structure, graphite grains are distributed in a ferrite matrix, the graphitization rate is 90% or more, and the pearlite fraction is less than 10%.

9. The graphite steel for TV pum nut parts according to claim 8, characterized in that the graphitization rate is 99% or more.

10. A step of manufacturing a wire containing, by weight percent, 0.60-0.79% carbon (C), 2.0-2.5% silicon (Si), 0.7-1.3% manganese (Mn), 0.2-0.5% sulfur (S), 0.01-0.05% aluminum (Al), 0.005-0.020% titanium (Ti), 0.003-0.015% nitrogen (N), 0.0001-0.015% phosphorus (P), with the balance being iron (Fe) and unavoidable impurities; and subjecting the wire rod to a graphitization heat treatment.

11. 11. The method of claim 10, wherein the graphitization heat treatment comprises performing heat treatment at a temperature in the range of 700 to 800° C. for 5 hours or more.

12. A cutting method, comprising cutting the graphite steel for TV pumnut parts according to claim 8 using a CNC compound lathe or a CAM automatic lathe.

13. 13. The cutting method according to claim 12, wherein the CNC combined lathe has a cutting speed of 1500 RPM or more and a transfer speed of 0.03 mm / rev or more.

14. 13. The cutting method according to claim 12, wherein the CAM automatic lathe has a cutting speed of 1500 RPM or more and a transfer speed of 0.03 mm / rev or more.

Citation Information

Patent Citations

  • Machine-structural carbon steel excellent in machiniability

    JP1995188847A

  • Graphite-compositive free cutting steel

    JP1996073989A

  • Steel for machine structure excellent in machinability

    JP2000034538A

  • Steel for machine structure superior in machinability

    JP2003034840A

  • Steel material for graphite steel, and graphite steel having enhanced machinability

    JP2019112711A